Through windows of opportunity : a neuroaffective approach to child psychotherapy - Bentzen, Marianne; Hart, Susan (Karnac Books, 2015)
This book explores some essential nonspecific factors of child psychotherapy. It is based on video transcripts and discussions of four outstanding child therapists during a two-day conference in Copenhagen in June 2013, pinpointing the moments of meeting and moments of change irrespective of method. Research has shown that nonspecific factors such as relationship and personality have a stronger correlation to outcome than method. The basic argument of The Science and Magic of Child Psychotherapy is that skilled psychotherapists do similar things while describing them differently, and that psych.